Enhancing Digital Literacy in Balongdowo Village for MSMEs Development through Digital Application Training - utomo, bedjo; luthfiyah, sari; triwiyanto, triwiyanto; Irvandi (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
The development of digital literacy is an important aspect in mastering digital marketing strategies, especially in the face of today's global competition, given the importance of digital literacy, the right product marketing strategy is needed to improve the digital competence of Micro, Small, and Medium Enterprises (MSMEs) through seminars and workshop assistance for UMKM entrepreneurs in Balongdowo village. The purpose of this community service activity is first to increase digital marketing knowledge and develop digital literacy of MSMEs business actors in Balongdowo Village, Candi District, Sidoarjo and the second is to implement Digital marketing applications (Istagram, Facebook, Sophee, Tokopedia platforms) through workshops and mentoring activities that focus on marketing village products involving resource persons who are experts in the field of digital marketing. The target of this activity is UMKM entrepreneurs and young entrepreneurs in the Balongdowo Village area. The results of this service activity show a significant increase in participants' knowledge and skills in utilizing technology to manage transactions and market MSMEs products. In addition, the participants were aware of the importance of digital security and ethics in the use of information. Overall, this activity succeeded in increasing the enthusiasm of UMKM actors to understand and apply digital marketing technology. And it is hoped that participants will be more prepared to compete positively, both at the local and national levels. In the future, it is hoped that continuous training can be held as a strategic step to ensure the sustainability of the use of technology in the management of MSME businesses in Balongdowo Village.